(untitled) (Bangladesh Critical Care Journal, 2014)
Aims: The study was aimed to evaluate vascular territories of infarcts involved in patients with stroke for the first time with diabetes on CT and/ or MRI of brain. Methodology: This cross sectional descriptive study was carried on a total of 100 adult patients with first ever stroke consecutively reported in the Department of Neurology, BIRDEM General Hospital, Dhaka, over a period of six months. Results: The mean age was 61.45 years and majority (35%) belongs to age group of 50-59. Ten (10%) subjects had age above 80 years. Male were 68% and 32% were female. Majority (89%) of the subjects had hemiplegia following acute stroke. Aphasia (71%), headache (39%), convulsion (23%), vomiting (18%) and cranial nerve palsy (17%) were also found. Additional preexisting risk factors were hypertension (72%), dyslipidaemia (59%), smoking (56%) and alcohol abuse (2%). Among the study subjects the diabetic complications were peripheral vascular disease (4% ), neuropathy (8%), nephropathy( 9%)and retinopathy(25%). CT scan and/ or MRI brain showed parietal lobe lesion in 57% cases. Majority (76%) had infarcts in middle cerebral artery territory. Involvement of anterior and posterior cerebral artery territory was found in 7% and 5% subjects respectively. Vertebro-basilar arterial system involvement was observed in 6% cases. 4% subjects had involvement of both middle and posterior cerebral arteries. Both anterior and posterior arterial territory infarcts were found in 2% cases. Conclusions: In conclusion most of the diabetic subjects with first ever ischemic stroke had involvement of middle cerebral artery. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19951 Bangladesh Crit Care J March 2014; 2 (1): 16-20